Using etesting methods in cs education - Armenski, Goce; Gushev, Marjan (My University, 2001)
This paper reports results from a study on using electronic testing tool for assessment of student knowledge in few university courses for CS education. The study was basically concerned with the effectiveness of using electronic testing tool for assessment purposes. The effectiveness was analyzed through cost savings and improvement of quality of the assessment process, viewed from both perspectives: the teacher perspective, and the student perspective. Data gathering took place over six semesters after which questionnaire was completed by the students through which their experiences and reactions were evaluated. Analysis of data about effectiveness viewed from teachers perspective was gathered through informal interviews with faculty members that administer and create computer-based tests.
Keywords: eTesting, eLearning, web-based assessment